Pengaruh Pengendalian Internal dan Asimetri Informasi Terhadap Kecenderungan Kecurangan Akuntansi - Aqilla, Difaf Sausan; Dwita, Sany (Universitas Negeri Padang, 2025)
This study aims to examine the effect of intenal control and assymetric information on the tendency of accounting fraud in the Regional Apparatus Organization (OPD) of Tanah Datar Regency. The sampling method used is purposive sampling with a total of 72 respondents consisting the head of OPD, the head of accounting and finance department, and the staff of accounting and finance department of each OPD. The source of data in this study are primary data and data collection techniques using a questionnaire. The result of this study indicates that (1) intenal control has a negative effect on the tendency of accounting fraud in the Regional Apparatus Organizaion (OPD) of Tanah Datar Regency, and (2) assymetric information has a positive effect on the tendency of accounting fraud in the Regional Apparatus Organizaion (OPD) of Tanah Datar Regency.